SPOTLIGHTING MINOR AND SIDE CHARACTERS BEYOND THE HERO’S DOMINANCE IN LITERARY WORKS - Rommel Utungga Pasopati; Kusuma Wijaya; Ni Nyoman Sarmi; Victor Maruli Tua L. Tobing; Rio Pratama Ramadan (LP2M UIN Abdul Muthalib Sangadji Ambon, 2026)
This study examines the evolving role of minor and side characters in narrative structures traditionally dominated by a central hero. Conventional storytelling in literature, film, and media has long prioritized the protagonist as the primary driver of plot and thematic meaning, often reducing secondary characters to limited, functional roles. This hero-centric model restricts the interpretive depth of narratives and overlooks the potential contributions of less notable individuals. Addressing this gap, the study explores how minor and side characters can function as complex, autonomous agents who enrich narrative development, provide alternative perspectives, and deepen thematic complexity. Using qualitative textual analysis across novels and films, the research investigates narrative techniques that decenter the hero, including multi-perspective storytelling, ensemble structures, and nonlinear narratives. The study is guided by key questions regarding the expanded roles of secondary characters, the strategies used to elevate them, and the broader cultural implications of redistributing narrative focus. Findings suggest that highlighting minor characters not only enhances audience engagement but also challenges hierarchical storytelling conventions and promotes inclusivity in representation. In conclusion, this research shows how minor and side characters are not trivial, yet they have independent stories that go beyond the singular dominance of the hero.